Factors affecting the likelihood of working abroad among UPV Iloilo graduating students. - Lim, Aldean Philip A.
The study identified the different factors that affect the willingness and likelihood to work abroad of UPV Iloilo graduating students., There were 103 respondents from four colleges of UPV in Miagao and Iloilo campuses who were included in the survey. The dependent variable was a dichotomous variable assuming a value of 1 if the respondent is willing to work abroad and 0 if otherwise. The independent variables considered in the study were classified into two broad characteristics namely: characteristics of possible migrants and non-migrants (sex, college, perception of the country's economic condition, perceived possibilities of employment and presence of relatives abroad) and a set of economic variables affecting willingness to work abroad (willingness to pay, maximum willingness to pay, and income differentials between source and receiving countries). The equation was estimated using binary logistic regression. The multivariate analysis revealed perception of the origin country's economic condition, presence of relatives, abroad, willingness to pay of the individual for the job intermediation cost, and income differential between the country of origin and destination country to be significant within 5 percent level of significance. The chi-square value, 42.474 which is also significant at 5 percent level shows that the whole model is very significant in determining the migration decisions of UPV graduating students.